Hydrodynamic Model Simulation of Cikidang River Estuary, Pangandaran based on Two Season in Indonesia - Sudradjat Supian, Hazman Hiwari, Titan Malik Ibrahim, Subiyanto (International Journal of Advanced Science and Technology, 2020)
Cikidang river estuary is located in Pangandaran Bay, which is directly opposite the coast. This condition highly influenced by the complex process of the ocean hydrodynamics. This paper aims to analyze the movement of currents at the estuary of Cikidang River, Pangandaran in two different seasons. In this paper, data of wind, tides, bathymetry, and coastlines are needed for simulation. Model simulations are performed using MIKE 21 HD software. In the west monsoon, the current moves eastward at a speed of 0.04 - 1.12 m/s. In the east monsoon, the current moves strongly toward the west range from 0.04 – 1.20 m/s. This is influenced by the movement of winds that move in the east monsoon ranging between 3-6 m / s with pairs of tides reaching 1.6 m. While the wind in the west season moves from the west with a speed of 1.2 - 4.8 m/s and a pair of tides reaching 1.4 m. Model validation in this study has error values ranging from 0.15 to 0.16%. This value of the model provides evidence that the model results obtained are the same as the field conditions or can be trusted.